Up-regulation of m6A writer METTL14 inhibits tumorigenesis by suppressing glycolysis in colorectal cancer - Lulu Li; Rong Zhang; Yongsheng Li (BMC Cancer)
Abstract Background Colorectal cancer (CRC) is a common malignant tumor. N6-Methyladenosine (m6A) modification plays an important role in the regulation of glycolysis in tumor cells and may be a potential target for tumor therapy. Methods The role of METTL14, an m6A writer, in CRC was investigated through functional assays including cell viability, colony formation, and glycolysis-related measurements (glucose uptake, lactate production, extracellular acidification rate (ECAR) and oxygen consumption rate (OCR)). The target gene regulated by METTL14 in an m6A-dependent manner was identified using molecular biology techniques. In addition, CRC cells overexpressing METTL14 were subcutaneously injected into mice to verify the regulatory effect of METTL14 on tumor growth in vivo. Results Our data suggested that METTL14 was up-regulated in CRC cell lines, and over-expression of METTL14 suppressed cell proliferation and glycolysis. Meanwhile, ATF2 m6A level was significantly up-regulated by over-expression of METTL14, and the binding relationship between ATF2 and METTL14 was further verified. METTL14-m6A regulated ATF2 in CRC cells participates in the regulation of glycolysis. METTL14 also suppressed tumorigenesis of nude mice. Conclusion Intervention with METTL14 mediated m6A modifications or its associated protein ATF2 may provide new strategies for CRC therapy.